Design Optimization Analysis of Ground Grid in Extra High Voltage Substation using ETAP Software - Shwe, Hnin Ei; Swe, Wunna (The Indonesian Journal of Computer Science, 2025)
The power system of Myanmar relies on the 500 kV substations. They provide the power needs of the entire power system while covering a huge region. Examining the substation's ground grid system thoroughly is necessary to safeguard the grid and maintain its functionality. The grounding system of the substation is thoroughly examined, incorporating practical data collection for detailed analysis. Special emphasis is placed on the application of the latest IEEE 81-2013 standards during the data collection phase. The analysis and modeling of the network are conducted using ETAP software version 19. Specifically, the Ground Grid System (GGS) module, available in the latest version of ETAP (version 19), is utilized for the study. The substation is planned for an extension, which includes the installation of a new power transformer. The addition of the new power transformer is anticipated to elevate the overall fault level of the substation. This increase in fault level is analyzed in a dedicated case study, and a potential solution is proposed. A new ground mesh is also designed for this area, serving as a benchmark for future substations in the region, ensuring that essential parameters are carefully considered. Additionally, a new ground mesh is designed for a 500 kV substation, as it is expected to become part of the national grid in the near future. This aligns with the ongoing feasibility study conducted by NCC in Myanmar for the establishment of the first 500 kV substation in the area. The impact of variations in ground grid resistance and key safety parameters, influenced by changes in ground grid mesh shape, depth, and size, is thoroughly explained using results derived from various scenarios.